Efficacy of the Web-Based Swedish Individualized Active Communication Education (I-ACE) Program in First-Time Hearing Aid Users: Randomized Controlled Trial - Louise Werther; Elisabet Sundewall Thorén; Jonas Brännström; Gerhard Andersson; Marie Öberg (Journal of Medical Internet Research)
Abstract BackgroundHearing loss is estimated to affect more than 20% of the global population. Hearing aid fitting is a common intervention in audiological rehabilitation; however, there are still those who struggle with remaining communication difficulties that require additional intervention. The group rehabilitation program Active Communication Education (ACE) has been shown to be an effective alternative for addressing these remaining difficulties. To increase accessibility, the ACE program was modified to an individual version. The effects of the Individualized Active Communication Education (I-ACE) are yet to be explored in a randomized controlled trial. ObjectiveThis study aims to explore the effects of the internet-based Swedish I-ACE program on the use of communication strategies, self-perceived hearing difficulties, and the emotional effects of hearing loss, as well as whether these effects persist long-term. MethodsFirst-time hearing aid users with 6‐12 months of experience with hearing aids were invited to participate in a randomized controlled trial. The participants were allocated to either the Swedish I-ACE intervention program or the delayed intervention control group. The 5 chapters of the I-ACE were delivered over a 5-week period through the nationally available online health portal for the public health system, 1177.se. Each week, feedback was provided through the platform by a clinician. The efficacy of the I-ACE was determined by change of the primary outcome of emotional consequences and acceptance of hearing loss, and use of communication strategies. The secondary outcome measures included perceived hearing difficulties, hearing aid efficacy, and intervention efficacy. Participants completed the self-assessed outcome measures at baseline (T0), post intervention (T1), and 6 months post intervention (T2) through the platform. ResultsA total of 57 participants (I-ACE, n=29 and delayed intervention control, n=28) were included in the analyses. Compared with the control group, the Swedish I-ACE improved the emotional consequences and acceptance of hearing loss, as well as use of communication strategies (the Communication and Acceptance Scale, F1, 54PF1, 53P ConclusionsThe results suggest that the I-ACE program can be an effective alternative for reducing emotional consequences of hearing loss and increasing the use of communication strategies to reduce remaining communication difficulties.